The nesting biology of ducks in the Marismas of the Guadalquivir, south-western Spain - Amat, Juan A (Wildfowl, 1982)
Duck nesting biology was studied during 1976-1978 on Doana National Park (Marismas of the Guadalquivir, SW Spain). In this period 8 duck species were found nesting on the area, but only Mallard Anas platyrhynchos, Gadwall A. Strepera, Red-crested Pochard Netta rufina, and Pochard Aythya ferina had important breeding populations. Pochard was the most selective Species when choosing nesting habitat and nesting cover. Diving ducks nested closer to the future feeding areas of ducklings than dabblers. Clutch-sizes (mean plus or minus 1 SE) were 8.7 plus or minus 0.1 for Mallard, 10.0 plus or minus 0.3 for Gadwall, 9.9 plus or minus 0.3 for Red-crested Pochard, and 8.7 plus or minus 0.2 for Pochard. A significant seasonal decrease in clutch-size was recorded for Mallard and Pochard. Nesting success varied from 62% (Pochard) to 48% (Mallard), and hatching success from 70% (Gadwall) to 48% (Red-crested Pochard). Nests were mainly deserted due to human influence and nest parasitism. Major duck nest predators in the Marismas were Ravens Corvus corax, kites Milvus spp. and rats Rattus sp. Nesting success was significantly greater for Mallard and Pochard, and marginally significant for Red-crested Pochard, when nesting occurred within Black-winged Stilt Himantopus himantopus colonies. Results are compared with those obtained by other authors.